Gender and age differences in parentchild conflict resolution tactics in Chinese and Belarusian families - Zhao, Silu; Fourmanov, Igor A. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
Gender and age differences in parent-child conflict resolution tactics in Chinese and Belarusian families are discussed. It is established that under the influence of Confucian culture the behaviour of Chinese parents resorting to violent tactics of conflict resolution is acceptable. It is determined that Belarusian families are characterised by a relatively egalitarian relationship, flexibility in problem solving, close intergenerational communication and open expression of emotions, which influenced Belarusian parents to choose non-aggressive methods to resolve conflict with their children regardless of their age.